The Imprint of the Picturesque on Nineteenth-Century British Fiction - Ross, Alexander M. (Book collections on Project MUSE., 2006)
Alexander M. Ross's book is a monograph in the best sense of the word: a short book on a single theme by a devoted expert. In recent years, with the increasing number of interdisciplinary ventures designed to break down the self-imposed barriers between specialist disciplines, there have been several studies of the relation of individual novelists - Eliot, Hardy, James - to the visual arts. But there have been few more general inquiries into the interconnections between fiction and painting. Ross has made good this deficiency in one important area. He has taken the cult of the picturesque,